We have to find the value of lim x--> -1 [(2x^2-x-3)/(x+1)]

If we substitute x = -1 in (2x^2-x-3)/(x+1) we get 0 / 0. So L'Hopital's theorem can be applied. We now have:

lim x--> -1 [(4x -1)/(1)]

substituing x = -1, we get (-4 - 1)/1

=> -5

** Limit...**

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the value of lim x--> -1 [(2x^2-x-3)/(x+1)]

If we substitute x = -1 in (2x^2-x-3)/(x+1) we get 0 / 0. So L'Hopital's theorem can be applied. We now have:

lim x--> -1 [(4x -1)/(1)]

substituing x = -1, we get (-4 - 1)/1

=> -5

**Limit = -5**